The ability to support accessible tourism in Chiang Mai, Thailand - Suprapa Somnuxpong (2020)
© 2020 AJHTL /Author/s. This research aimed to study the readiness of Chiang Mai to support the market of those who are disabled in some way and need special access. This article considers the support of marketing management for this group of tourists by referring to the tourist attractions that have cited the preparation for accessing the market of this group of people. The research was qualitative and the sample group consisted of 5 sample groups as follows. A group of tourists with special access demands, product and service providers in that place or the attraction, tour guides and tour agencies, government agencies and NGOs. The results from the visitors' point of view show that all the seven studied places in Chiang Mai are still not ready to be accessed because they lack facilities such as ramps, designated parking lots, pathways and suitable toilets. Moreover, from the research results according to the visitors' experience, it cannot be concluded that all these seven places have the readiness to provide the accessibility information and would in any way be able to contribute to the visitors in providing this because none of the visitors are also not prepare themselves to collect all the needed information relating to disability provision from these places before their trips. The results show that most of the tourists do not pay attention to systematically learn about their targeted destinations. Nevertheless, all the servicers are gradually developing and venues are slowly improving their services in both the needed physical aspects and data service access in order to provide more convenience to all the tourists in Chiang Mai.